Activation timing of soleus and tibialis anterior muscles during sit-to-stand and stand-to-sit in post-stroke vs. healthy subjects. (March 2013) - Silva, Augusta; Sousa, Andreia S. P.; Pinheiro, Rita; Ferraz, Joana; Tavares, João Manuel R. S.; Santos, Rubim; Sousa, Filipa
<x xml:space="preserve">Abstract</x> Introduction. Sit-to-stand (SitTS) and stand-to-sit (StandTS) are very important functional tasks that become compromised in stroke patients. As in other voluntary movements, they require an adequate postural control (PC) involving the generation of anticipatory postural adjustments (APAs). In order to give clues for more efficient and directed rehabilitation programs, a deeper knowledge about APAs during challenging and daily life movements is essential. Purpose. To analyze the activation timing of tibialis anterior (TA) and soleus (SOL) muscles during SitTS and StandTS in healthy subjects and in post-stroke patients. Methods. Two groups participated in this study: one composed of ten healthy subjects and the other by ten subjects with a history of stroke and increased H-reflex. Electromyographic activity (EMGa) of SOL and TA was analyzed during SitTS and StandTS in the ipsilateral (IPSI) and the contralateral (CONTRA) limb to the side lesion in stroke subjects, and in one limb in healthy subjects. A force plate was used to identify the movement onset. Results. In both sequences, in the stroke group SOL activation timing occurred prior to movement onset, contrary to the pattern observed in the healthy subjects. Statistically significant differences were found in SOL activation timings between each lower limb of the stroke and healthy groups, but no significant differences were found between the IPSI and the CONTRA limb. The TA activation timing seems to be delayed in the CONTRA limb when compared to the healthy subjects and showed a better organization of TA timing activation in StandTS when compared to SitTS. Conclusion. Compared to healthy subjects, APAs seem to be altered in both limbs of the post-stroke subjects, with the SOL activation timing being anticipated in both SitTS and StandTS.